2017
DOI: 10.1108/jmd-03-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

An enquiry into potential graduate entrepreneurship

Abstract: Purpose In today’s global economy, high in talent but low in growth, the capability and skills mismatch between the output of universities and the demands of business has escalated to a worrying extent for graduates. Increasingly, university students are considering alternatives to a lifetime of employment, including their own start-up, and becoming an entrepreneur. The literature indicates a significant disconnect between the role and value of education and healthy enterprising economies, with many less-educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Conflicts often arise between the interests of family members and those of the overall company. A wellplanned management succession program is needed to ensure that family firms can balance personal interests without sacrificing professionalism, while laying the groundwork for the success of the business well into the future (Mokhber et al, 2017).…”
Section: The Challenges Of a Family-run Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts often arise between the interests of family members and those of the overall company. A wellplanned management succession program is needed to ensure that family firms can balance personal interests without sacrificing professionalism, while laying the groundwork for the success of the business well into the future (Mokhber et al, 2017).…”
Section: The Challenges Of a Family-run Businessmentioning
confidence: 99%
“…Previous studies have shown that some family firms focus only on the transfer of ownership between family members in a company and do not thoroughly address the need for a structured succession plan (Mokhber et al, 2017). Ignoring the serious business of long-range succession planning, they tend to focus on short-term flexible plans and to believe that all is well as long as the company generates enough revenues to be profitable.…”
Section: A Stated Desire To Be Sustainablementioning
confidence: 99%
“…For universities, the following factors of regional innovative development are important:  flexible and creative thinking, the ability to generate and implement new breakthrough ideas, high innovative adaptability (Birch, 2017);  development of students' entrepreneurial competencies (Chepurenko et al, 2019);  broad support for entrepreneurial activities of youth and students (Golovko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Afonosova points out that in the context of digital transformation of economy only higher education can become the driver of innovation development and stability of economic growth [2]. C. Birch, J. Lichy, G. Mulholland, M. Kachour believe that forming and encouraging flexible thinking, creativity, supporting the testing of new ideas and ways of implementing them, adapting to innovations are extremely important future factors of innovation development and the foundation for them can be formed only at higher education institutions [4].…”
Section: Introductionmentioning
confidence: 99%